Lalabet Financial Analysis: Study of Islamic Economics at Micro Level - Ainorrofiqie, Ainorrofiqie; Khasanah, Umrotul; Djalaluddin, Akhmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
This research aims to explore the model of financial management tradition Lalabet in the village of Babbalan District Batuan Sumenep. This study is based on the fact that occurred in the community about the implementation of traditions carried out by the heirs to family members who died. Interpretative qualitative research is used and an in-depth understanding of a problem that occurs is emphasized more. Based on the results of this study, the financial management tradition Lalabet can be done based on accounting equations. The accounts contained in the accounting equation is not used in its entirety and are reported as are generally financial statements. In this case, the source of funds in carrying out Lalabet tradition is sourced from personal money, money and donations from the family, money from Muslimat, debt, and money or goods from Lalabet's proceeds. The impact is the onset of debt both short-term and long-term. While the expenditure is in the form of costs in taking care of the body, costs for tahlilan (petto'arean), pa'polo, nyatos, nyataon, nyaebu, mangaji, ngin-tangin, nyalenin mayyid, and ajege makam (kep-sekep).